Case Report: Successful therapy with all-trans retinoic acid combined with chemotherapy followed by hematopoietic stem cell transplantation for acute promyelocytic leukemia carrying the BCOR-RARA fusion gene - Chen, Li; Zhu, Hongming; Zhu, Yongmei; Jin, Wen; Dong, Fangyi; Li, Jianfeng; Hu, Jiong; Chen, Qiusheng; Wang, Kankan; Li, Junmin (Frontiers in Oncology, 2022)
Acute promyelocytic leukemia (APL) is characterized by the balanced translocation of chromosomes 15 and 17, resulting in the formation of PML-RARA fusion gene. More than 98% of APL have PML-RARA fusion, and less than 2% have other types of RARA gene partners, which named variant APL (vAPL). In the present study, we reported a vAPL with BCOR-RARA, which was the third case of BCOR-RARA APL published. The patient achieved complete remission (CR) with all-trans retinoic acid (ATRA) monotherapy, and molecular CR with ATRA plus standard chemotherapy. After that, he underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT) and ATRA maintenance and maintained a molecular CR status. This case provided valuable insights into the accurate identification of vAPL. Moreover, ATRA combined with chemotherapy followed by allo-HSCT was suggested as an optimal choice for those vAPL patients who had a high risk of relapse.